CCTV in Australia (ADA Dataverse, 2019)
This research involved a national online survey of local councils in Australia, conducted in mid-2014. An invitation to participate in the survey was sent to all 561 councils in each state and territory (with the exception of the ACT) via a letter to the CEO and an email to the front desk or generic council email address. Several reminder emails were sent encouraging councils to participate in the research, and incentives were offered to participants. The survey was open for approximately six weeks between May and June 2014. A total of 221 councils completed the survey by the end of the data collection period, a response rate of 39 percent. Data were weighted using ABS population data for local government areas to ensure responses were representative of all councils. Population data were used because the number of residents influences council revenue (via rates), and councils with higher revenue may be more able to afford the installation of CCTV (or larger CCTV systems). Larger councils (in terms of population) may also be more likely to have CCTV because crime is typically more common in densely populated areas. Preliminary analysis of the data indicated that the achieved sample had disproportionate number of larger councils. All questions in this survey are about open-street closed circuit television (CCTV) systems. Open-street CCTV systems are surveillance systems established to monitor public spaces. The overall aim of this research was to develop a national picture of the prevalence and characteristics of open-street CCTV systems in Australia managed by local councils.